Prevalence and Determinants of Falls among Older Adults in Ecuador: An Analysis of the SABE I Survey. (7th February 2013) - Orces, Carlos H.
Abstract : The present study based on a nationally representative sample of older adults living in the Andes mountains and coastal region of the country indicates that 34.7% of older adults had fallen in the previous year in Ecuador. Among fallers, 30.6% reported a fall-related injury. The prevalence of falls was higher in women and among older adults residing in the rural Andes mountains. In the multivariate model, women, subjects with cognitive impairment, those reporting urinary incontinence, and those being physically active during the previous year were variables found independently associated with increased risk of falling among older adults in Ecuador. Moreover, a gradual and linear increase in the prevalence of falls was seen as the number of risk factors increased. Falls represent a major public health problem among older adults in Ecuador. The present findings may assist public health authorities to implement programs of awareness and fall prevention among older adults at higher risk of falls.